Prevalence and imaging characteristics of nasopharyngeal and eustachian tube tonsilloliths in 2244 patients determined using computed tomography - Takahashi, Akira; Sugawara, Chieko; Akita, Kazuya; Kamada, Kumiko; Kudoh, Keiko; Tamatani, Tetsuya; Miyamoto, Youji (Dento-maxillo-facial radiology, 2018)
Nasopharyngeal tonsilloliths (NT) and eustachian tube tonsilloliths (ET) are not as well-known to radiologists as palatine and lingual tonsilloliths. The aim of this investigation was to determine the prevalence and imaging characteristics of NT and ET using CT and panoramic radiographs. We retrospectively assessed the scans of 2244 patients who underwent consecutive CT and panoramic radiographs of the maxillofacial region. The prevalence, size, number, and position of NT and ET were analysed. NT and ET were detected in 14 (0.6%) and 6 (0.3%) of 2244 patients on CT, respectively, but they were undetectable on panoramic radiographs. No significant difference was found in the prevalence with respect to sex. Although there was also no significant difference in the prevalence among age groups, tonsilloliths were most commonly noted in patients over 40 years old; they appeared as small and round calcified bodies, ranging from 1 to  3 mm in diameter. All NT were found 0 to 3 mm beneath the nasopharyngeal mucosal surface. The prevalence of NT and ET on CT was lower than that of palatine and lingual tonsilloliths. However, since they are encountered more frequently than clinically significant calcifying diseases such as retropharyngeal calcific tendinitis, clinicians should be able to correctly diagnose NT and ET based on their anatomical features.